From the Chiang Mai Initiative to an Asian Monetary Fund - Masahiro Kawai (Asian Development Bank Institute (ADBI), 2015)
Following the 1997-1998 Asian financial crisis, financial authorities in ASEAN+3 embarked on several new initiatives for East Asia's financial cooperation, including: (i) regional economic surveillance led by the Economic Review and Policy Dialogue (ERPD); (ii) a regional liquidity support facility, called the Chiang Mai Initiative (CMI); and (iii) local-currency bond market development. The global financial crisis of 2007-2009 demonstrated the need to further strengthen East Asian financial cooperation. This paper summarizes and evaluates the progress of regional financial cooperation, particularly the ERPD, the CMI and its subsequent multilateralization (CMIM), and the ASEAN+3 Macroeconomic Research Office (AMRO). It identifies the challenges in strengthening the CMIM, ERPD, and AMRO and suggests that the CMIM and AMRO be transformed into an Asian monetary fund (AMF). The paper argues that for an AMF to emerge, ASEAN+3 authorities need to: (i) contribute part of their foreign exchange reserves to the fund; (ii) establish a secretariat in charge of all aspects of the CMIM, including its activation; and (iii) delink the CMIM from the International Monetary Fund (IMF) programs by upgrading their capacity to conduct regional surveillance, formulate independent conditionality associated with crisis lending, and monitor policy and economic performance. In the transition period, eligible member countries should be allowed to have more flexible access to the CMIM facility. The CMIM and AMRO should work with the IMF to promote East Asian financial stability, but at the same time the IMF needs to undertake significant operational and governance reforms so that it regains the trust of emerging economy members in the region.
Keywords: F33; F36; 330; chiang mai initiative; asian monetary fund; bond market development; crisis lending; multilateralization